The Effectiveness of the Bride-to-be Course in Reducing the Divorce Rate at the Religious Affairs Office of Karossa District Central Mamuju Regency - Nur Isra Kurnia; Mukhlis Bakri; Muh Chiar Hijaz (Journal of Family Law and Islamic Court, 2025)
This study aims to examine the effectiveness of the implementation of Suscatin in KUA Karossa District, as well as to analyze the supporting and inhibiting factors in its implementation. This study uses a qualitative descriptive method (Field research), with data collection techniques in the form of observation, interviews, and documentation. The research subjects consisted of the head of KUA, Islamic religious extension workers, and course participants. Data analysis is carried out through the process of data reduction, data presentation, and conclusion drawn. The results of the study show that Suscatin at KUA Karossa has been implemented in accordance with technical instructions from the Ministry of Religious Affairs, and has a fairly good effectiveness in providing an understanding of the rights and obligations of husband and wife, communication in the household, and conflict management. This can be seen from the increasing awareness of brides-to-be on the importance of readiness before marriage, and the decrease in divorce rates after the program is carried out regularly. Supporting factors in the implementation of this program include the existence of active religious extension workers, cross-agency cooperation, and community support. Meanwhile, the inhibiting factors are limited facilities, and lack of operational funds.